Achievement and under-achievement in Sri Lanka:a survey of Navodaya scholarship winners - Jayaweera, S.; Gunawardhana, R. (My University, 1980)
Abstract available from Library, Please quote title when requesting
Keywords: University education; Secondary education; Primary education; Scholarship scheme; Education